2018
DOI: 10.4103/ijn.ijn_43_18
|View full text |Cite
|
Sign up to set email alerts
|

Role of blood oxygen level-dependent MRI in differentiation of acute renal allograft dysfunction

Abstract: Early graft dysfunction after renal transplantation manifests as acute rejection (AR) or acute tubular necrosis (ATN). Blood oxygen level-dependent (BOLD) magnetic resonance (MR) imaging is a noninvasive method of assessing tissue oxygenation, which may be useful for predicting acute allograft dysfunction. This was a prospective study involving 40 patients scheduled for renal transplantation from August 2012 to August 2014. In addition, 15 healthy donors were also enrolled in this study. All recipients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In a study of 40 patients conducted by Lal et al (19) to evaluate BOLD-MRI using 3 T (32 normally functioning transplants, six with biopsy-proven acute rejection, and two with biopsy-proven ATN), they found that in the acute rejection group, the mean cortical R2* and mean medullary R2* values were significantly lower compared with ATN and normal function graft groups. They also found that ATN allografts showed increased R2* values in the cortex and medulla, which is similar to our observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 40 patients conducted by Lal et al (19) to evaluate BOLD-MRI using 3 T (32 normally functioning transplants, six with biopsy-proven acute rejection, and two with biopsy-proven ATN), they found that in the acute rejection group, the mean cortical R2* and mean medullary R2* values were significantly lower compared with ATN and normal function graft groups. They also found that ATN allografts showed increased R2* values in the cortex and medulla, which is similar to our observation.…”
Section: Discussionmentioning
confidence: 99%
“… Values are given as mean ± SD, unless otherwise indicated. This is a modified table after Lal et al (19). AR, acute rejection; ATN, acute tubular necrosis; CR2*, cortical R2*; MCR, medullary over cortical R2* ratio; MR2*, medullary R2*; MRI, magnetic resonance imaging. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has ( 21 ) reported higher R2* values in patients with acute rejection than in those without rejection. A previous study ( 22 ) showed that acute tubular necrosis (ATN) and AR patients had lower R2* values than functionally normal allograft patients. Another study ( 23 ) reported that the medullary R2* values were lower in transplanted kidneys than native kidneys, which may be due to increased blood flow due to allograft debulking.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have used 3 Tesla (3T) magnets, which allow for higher spatial resolution and better visual differentiation between the renal cortex and medulla. (1,5,7,8)…”
Section: ❚ Introductionmentioning
confidence: 99%